Integrating Culture into Language Instruction: Enhancing Speaking Skills at SMAN 3 Pangkalpinang - Akbar, Lingga Oka; Hermansyah, Hermansyah; Mayasari, Santi (ELT Worldwide: Journal of English Language Teaching, 2023)
This study explored the integration of cultural components in speaking skills instruction at SMAN 3 Pangkalpinang. Utilizing a descriptive qualitative approach, data was sourced from a questionnaire given to 130 students and interviews with two teachers. Secondary data was extracted from documentation. Multiple cultural components were identified as beneficial for speaking instruction, including intellectual values, lifestyle behaviors, media, artistic values, family, minor values, major values, and formal values. These components exhibited mutual support, rendering them inseparable. Both educators and students acknowledged the effectiveness of integrating these components in enhancing English oral proficiency. The intertwined nature of the cultural components suggests a need for a holistic approach to language instruction, emphasizing both linguistic and cultural elements. Educational institutions should consider adapting their curricula to incorporate these components, ensuring a comprehensive understanding of language and its associated cultural nuances. Furthermore, educators require training to effectively weave these components into their teaching strategies. The unanimous positive feedback indicates that such integration not only bolsters linguistic capabilities but also enriches overall communication skills. Incorporating cultural components into language instruction presents a promising strategy for enhancing speaking skills, with significant implications for curriculum design, pedagogical approaches, and improved language outcomes.